Factors associated with chronic calcineurin inhibitor nephrotoxicity in children with minimal-change disease - Bei Jin; Ziji Lu; Cheng Cheng; Yuxin Pei; Lizhi Chen; Zhihui Yue; Aihua Lin; Shicong Yang; Ying Mo; Xiaoyun Jiang (Renal Failure)
Background Calcineurin inhibitors (CNIs), such as cyclosporine (CsA) and tacrolimus (TAC), are commonly used to treat children with complicated minimal change nephrotic syndrome. However, chronic nephrotoxicity associated with CNIs poses a significant safety concern. This study aimed to identify the risk factors that contribute to chronic nephrotoxicity in these patients.Material and methods Clinical and pathological data of MCD children treated with CsA or TAC in our center between 1 January 2003 and 31 December 2022, were retrospectively reviewed. Kidney biopsies were performed on 80 patients who received CNI treatment for more than 6 months.Results Chronic CNI nephrotoxicity (striped interstitial fibrosis with tubular atrophy) was observed in 15% (12/80) of patients. Higher CNI culminating amounts were shown in patients who developed nephrotoxicity regardless of CsA or TAC treatment. Risk factors for chronic CNI nephrotoxicity included persistent nephrotic-range proteinuria for more than 30 days during CNI treatment, increased urinary NAG level, and CNI resistance. Multivariate analysis revealed that increased urinary NAG level and CNI resistance were the independent risk factors for chronic CNI nephrotoxicity in children with MCD.Conclusion MCD children who developed CNI resistance were susceptible to chronic CNI nephrotoxicity. Urinary NAG might be a valuable biomarker for CNI nephrotoxicity prediction in MCD children.